Comparative assessment of mortality risk factors between admission and follow-up models among patients hospitalized with COVID-19. (April 2021) - Lazar Neto, Felippe; Salzstein, Guilherme A.; Cortez, André L.; Bastos, Thaís L.; Baptista, Fabíola V.D.; Moreira, Joanne A.; Lauterbach, Gerhard P.; de Oliveira, Julio Cesar; de Assis, Fábio C.; Aguiar, Marília R.A.; de Deus, Aline A.; Dias, Marcos Felipe D.S.; et al.
Highlights: The inclusion of follow-up improved mortality prediction compared with admission for patients hospitalized with COVID-19. Vital signs mortality hazards were under-estimated at admission. DHL, urea, CRP and NLR could help prognosis of patients during follow-up. Abstract: Objectives: This study aimed to compare differences in mortality risk factors between admission and follow-up incorporated models. Methods: A retrospective cohort study of 524 patients with confirmed COVID-19 infection admitted to a tertiary medical center in São Paulo, Brazil from 13 March to 30 April 2020. Data were collected on admission, and the third, eighth and fourteenth days of hospitalization. The hazard ratio (HR) was calculated and 28-day in-hospital mortality risk factors were compared between admission and follow-up models using a time-dependent Cox regression model. Results: Of 524 patients, 50.4% needed mechanical ventilation. The 28-day mortality rate was 32.8%. Compared with follow-up, admission models under-estimated the mortality HR for peripheral oxygen saturation <92% (1.21 versus 2.09), heart rate >100 bpm (1.19 versus 2.04), respiratory rate >24/min (1.01 versus 1.82) and mechanical ventilation (1.92 versus 12.93). Low oxygen saturation, higher oxygen support and more biomarkers–including lactate dehydrogenase, C-reactive protein, neutrophil-lymphocyte ratio, and urea remained associated with mortality after adjustment for clinical factors at follow-up compared with only urea and oxygen support at admission. Conclusions: The inclusion of follow-up measurements changed mortality hazards of clinical signs and biomarkers. Low oxygen saturation, higher oxygen support, lactate dehydrogenase, C-reactive protein, neutrophil-lymphocyte ratio, and urea could help with prognosis of patients during follow-up.